2018
DOI: 10.1039/c8ra03697g
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable Pd/CuFe2O4 nanowires: a highly active catalyst for C–C couplings and synthesis of benzofuran derivatives

Abstract: Efficient heterogeneous Pd/CuFe2O4 nanowires which catalyze cross coupling transformations are described. The protocol is applied to a one-pot synthesis of benzofurans via Sonogashira coupling and an intramolecular etherification sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Results revealed that GO@FclÀ Pd 0.1 /Cu 0.9 monolayer with proper ligand, organometallic matching, ratio of different and preparation order could preserve the beneficial catalytic activity due to a positive synergistic. [26][27][28] The strategy suggested the great potential fundamental research could efficiently boost activity with multimetallic molecular monolayer. Considering of the cost and environmental requirements, GO@FclÀ Pd 0.1 /Cu 0.9 was selected as the following studies.…”
Section: Influences Combination Of Pd/m and Different Ratio Of Pd /Cu...mentioning
confidence: 99%
See 2 more Smart Citations
“…Results revealed that GO@FclÀ Pd 0.1 /Cu 0.9 monolayer with proper ligand, organometallic matching, ratio of different and preparation order could preserve the beneficial catalytic activity due to a positive synergistic. [26][27][28] The strategy suggested the great potential fundamental research could efficiently boost activity with multimetallic molecular monolayer. Considering of the cost and environmental requirements, GO@FclÀ Pd 0.1 /Cu 0.9 was selected as the following studies.…”
Section: Influences Combination Of Pd/m and Different Ratio Of Pd /Cu...mentioning
confidence: 99%
“…[18][19][20][21] Multimetallic catalyst containing Pd, Fe and Cu can yield high turnover frequency or number (TOF, TON) and efficiency, which have emerged as reliable, costeffective, "drop-in" options. [22][23][24][25][26][27] There are difficulties for developing and designing efficient multi-metallic catalysts, such as the preparation method, each component assembling, electronic effects controlling, active center distribution, which must be overcome. [28] Self-assembly way is usually used to construct structure desired, offering controllable orientation, thickness and stable films.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Most of these approaches are associated with terminal alkenes or alkynes effectively coupled/cyclized with various ortho-halogenated phenol. This was achieved by using various metalbased catalyst including palladium, [18] copper, [19] gold, [20] zinc, [21] iron, [22] and Rhodium. [23] In addition, few metal-free approaches are developed for the synthesis of substituted benzofurans involving one-pot tandem CÀ C bond coupling/cyclization, [24] one-pot cascade, [25] [3,3]-sigmatropic rearrangement of Ntrifluoroacetylene-hydroxylamines, [26] intramolecular Wittig reaction, [27] and aza-Michael/Michael/annulation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few methods based on “green” chemistry starting from easily accessible materials have been developed (Scheme 1, Path 2), which involve microwave-aided synthesis, 21–24 electrochemical catalysis, 25,26 and nanoparticle catalysis. 27,28…”
Section: Introductionmentioning
confidence: 99%